Professional Work Model in Terms of Standard Operating Procedures, Intelligence, Rules and Ethics - Rahman, Aufa (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
Working professionally is a moral responsibility in meeting the demands of stakeholders. Because in truth, working professionally is quality, providing satisfaction, solving problems, being effective, efficient, facilitating, ethical and responsible. Therefore, management leaders need to make efforts to build a professional work model by presenting a standardized work system, providing training to increase intelligence, and establishing ethical rules to establish integrity. This study aims to analyze the model of professional work in terms of work procedures, intelligence, ethics and rules. To test the research objectives, a qualitative approach was used with the SWOT analysis method. The unit of analysis in this research is civil service police in Sumbawa district. Research data was collected by means of in-depth interviews with 12 civil service police who met the criteria. The results of the study suggest that being professional at work is greatly influenced by many factors, one of the most dominant being the level of intelligence. Intelligence plays a very big role in behaving, behaving, making decisions, solving problems, directing and reconciling, and so on. Other factors that also shape work professionalism are work procedures and ethical codes. These two things serve as guidelines for civil service police to be able to discipline themselves so that they can carry out their duties according to the rules and not pose a risk.